Meningkatkan Kemampuan Siswa dalam Menganalisis Materi Descriptive Text Melalui Metode Two Stay Two Stray pada Mata Pelajaran Bahasa Inggris Kelas XII SMK Negeri 9 Padang - Raehan Anwar (Journal of Research and Investigation in Education, 2026)
This study aims to improve students' ability to analyze descriptive text material through the Two Stay Two Stray Stray method in English subjects for class XII of SMK Negeri 9 Padang. This method uses Classroom Action Research (CAR) which is a plan carried out by a teacher or prospective teacher to develop teaching methods, competencies, content and to achieve the objectives of the teaching and learning process can take place in a measurable and effective manner. The subjects of this study were class XII Hospitality 1, totaling 31 people. The results of this study indicate that students have been active in the teaching and learning process in each cycle. Students are more confident in analyzing the material being taught. In the data that has been obtained, there is an increase in scores on the results of the Post Test in cycle II compared to the Pre-Test in cycle I which increased by 31.39%. Researchers concluded that the use of the Two Stay Two Stray method can improve students' ability to analyze Descriptive Text material.